Assessment of knowledge, attitude and practices towards research; the perspectives of dental graduates - MUHAMMAD ABUBAKAR; MUHAMMAD HADEER RABBANI; MUHAMMAD SHEHZAD; HAZIQ WASEEM; TALHA AHMAD MALIK; RAFID AHMAD MALIK; SAJID NAEEM; KHEZRAN QAMAR (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Research is a systematic approach to reasoning and documenting clinical observations and problems that we encounter in clinical settings. It is a prerequisite for developing new skills and knowledge by all medical and dental professionals, which is beneficial for society. Aim: To assess research related knowledge, attitude, and practices among dental undergraduate and graduate students of a private dental college in Lahore city. Methods: Cross sectional with survey design was used in Dental College of Lahore Medical and Dental College, Lahore. The study took place between April 1st and July 1st, 2024. A total of 180 graduates and undergraduates of the college were selected. Data collection was done using a self-administered, structured, validated questionnaire. The questionnaire was divided into sections including sociodemographic factors, research knowledge, attitude, and research experience questions. For assessing knowledge, 10 dichotomous questions of true and false statements were used. A 5-point Likert scale (strongly disagreed, disagreed, neutral, agreed, and strongly agreed) was used to assess the attitude towards research; 7 positive and 7 negative questions were asked. Results: A total of 180 participants 31.3% males and 68.9% females—were selected. 69.4% were graduates, and 30.6% were undergraduates. One-way ANOVA significance was found for knowledge and practices towards research with respect to age groups p<0.05; however, an insignificant result was found with respect to attitude. Independent sample t test for gender and knowledge was insignificant p > 0.05. Insignificant result found for gender and practice; however, for attitude, significant result obtained; p<0.05. Statistically significant results obtained for knowledge, attitude, and practices towards research with graduates and undergraduates, i.e., p<0.05. Conclusion: The dental undergraduates and graduates’ students demonstrated good research knowledge and a positive attitude towards scientific research conduct, but the research practices were very low. Students should be actively engaged in research by making system-based reforms with respect to basic research knowledge and guidance to promote research culture. Keywords: House Officers, Research, Knowledge, Assessment, graduates,